Influence of work-life balance on organizational decision-making by accountants - Rother, Leonei; Vieira, Anelize Lopes; Vogt, Mara; Fabris, Juliana; Leite, Maurício (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: To analyze the influence of Work-Life Balance on organizational decision-making by accountants. Methodology: Descriptive, survey and quantitative. Data collection is carried out through a questionnaire sent via electronic mail, through the Conselho Regional de Contabilidade of Santa Catarina to accountants registered in the state. The sample consists of 96 respondents. For data analysis, the structural equation modeling technique is applied. Results: It was demonstrated that the balance between work and personal life is necessary to make more assertive decisions in the organizations in which accountants work so that they are not harmed by unstable environments they might be in. The importance given to the balance between work and personal life by the respondents and to the systemic approach related to organizational decision-making is clear. It is possible to conclude that the balance between work and personal life influences the organizational decision-making of accountants. Contributions of the Study: This study contributes in demonstrating the relevance of a balance in the lives of accounting professionals, given its impact on decisions made within the organizational environment and which impact clients and families, whether directly or indirectly.